IDEASI HUMANISASI DALAM ARTIFISIAL INTELEGENSI: NARRATIVE RIVIEW TENTANG PRAKTIK AI-BRAINSTORMING TERHADAP KETERAMPILAN MENULIS SISWA SMA - Rahma, Adelia; Enik Mukhoiyaroh Bambang, Siti; Octavia Kusuma Wardani, Diah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing skills in high school students require students' ability to generate and develop ideas logically and critically, however the conventional brainstorming process is often hampered by social pressure and limited perspective. This research aims to examine the role of artificial intelligence (AI) in supporting idea generation, variation of perspectives, and the emergence of unusual ideas in pre-writing brainstorming, as well as analyzing the contribution of AI to the formation of logical, coherent, and elaborated argumentation structures in upper secondary students. The method used is a literature review of 30 research articles sourced from Google Scholar, ResearchGate, and accredited national journals spanning the years 2020–2025. Narrative review research approach that refers to four dimensions of divergent thinking: fluency, flexibility, originality, and elaboration. The study results show that the integration of AI in pre-writing brainstorming consistently strengthens these four dimensions; AI increases the smoothness of idea generation, expands the variety of perspectives, encourages the emergence of more original ideas within the framework of human-AI co-creativity, and facilitates the elaboration of ideas into more mature argumentation structures. However, its effectiveness really depends on whether students' interaction patterns are active-dialogical or passive-receptive as well as on the quality of the teacher's pedagogical assistance. It is hoped that AI has the potential to become a meaningful cognitive partner in learning to write, as long as it is supported by a reflective, humanistic and ethical learning design to prevent the risk of dependency and reduction of originality.